Hydrochloric acid concentration and time to maximize lead and cadmium removal in laboratory wastewater (LACCEI, 2024)
Abstract- Bioadsorption treatment of wastewater from a university chemical analysis laboratory was carried out using Chondracanthus chamissoi "mococho" algae as biomass, under study factors: hydrochloric acid concentration (1 and 2 N) and contact times (2 and 7 h) in a continuous flow bioreactor, in order to determine the combination of factors that maximize the removal of Lead (Pb) and Cadmium (Cd). A 2k factorial design with central points and the response surface method were used from the results it was found that the combination of the factors hydrochloric acid (HCl) concentration and contact time that maximizes the removal of Pb ions are 2.5 N and 6.8 h and the combination of the factors that maximizes the removal of Cd ions are 2.1 N and 22 h, determining that the study factors generate statistically significant differences in the removal of Pb and Cd.